PENGARUH LAMA PEREBUSAN TERHADAP KARAKTERISTIK LOLOH DON PIDUH (Centella asiatica L.) - Putra, I Gusti Ngurah Arry; Yusasrini, Ni Luh Ari; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPA, 2019)
This study aims to determine the effect of boiling time to the characteristics of loloh don piduh (Centella asiatica L.) and the appropriate boiling time to produce loloh don piduh with the best characteristics. The experimental design used was a complete randomized design with 6 treatment levels: T1 (25 min utes ), T2 (40 min utes ), T3 (55 min utes ), T4 (70 min utes ), T5 (85 min utes ) and T6 (100 min utes ). The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with Duncan test. The boiling time had a very significant effect on antioxidant activity, vitamin C levels, and the level of panelist preference s for taste and overall acceptance of loloh don piduh . Boiling time had a significant effect on total soluble solids (TSS) of loloh don piduh. Boiling time had no significantly affect on panelist preference s for the color and flavor of loloh don piduh. 25 minutes boiling time had produced loloh don piduh with the best characteristics of: antioxidant activity 90,8 2 %, vitamin C levels  0,11%, total soluble solids (TSS) of 2 o brix, panelist preference s for color, flavor, taste , and overall acceptance was preferred.